2019
DOI: 10.4062/biomolther.2019.103
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Simultaneously Induces Both Apoptosis and Autophagy in Human Gastric Adenocarcinoma Cells

Abstract: Fluoxetine is used widely as an antidepressant for the treatment of cancer-related depression, but has been reported to also have anti-cancer activity. In this study, we investigated the cytotoxicity of fluoxetine to human gastric adenocarcinoma cells; as shown by the MTT assay, fluoxetine induced cell death. Subsequently, cells were treated with 10 or 20 μM fluoxetine for 24 h and analyzed. Apoptosis was confirmed by the increased number of early apoptotic cells, shown by Annexin V-propidium iodide staining. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The anticancer properties of fluoxetine were confirmed in many cancer models, both in vitro and in vivo [98,99]. However, some recent studies support its pro-survival potential as well [100,101]. An example of antiarrhythmic agents that can be potentially used in anticancer therapy is verapamil.…”
Section: Anticancer Therapies Targeting Ion Channelsmentioning
confidence: 99%
“…The anticancer properties of fluoxetine were confirmed in many cancer models, both in vitro and in vivo [98,99]. However, some recent studies support its pro-survival potential as well [100,101]. An example of antiarrhythmic agents that can be potentially used in anticancer therapy is verapamil.…”
Section: Anticancer Therapies Targeting Ion Channelsmentioning
confidence: 99%
“…Besides, FLX induces both, protective autophagosome formation and apoptosis simultaneously in vitro. However, autophagy inhibition enhances FLX-induced apoptosis through decrease p-Akt and increase DR4 and DR5 expression (16). Moreover, it has been reported an improved anti-proliferative effect due to FLX/paclitaxel combination on GACs (AGS cell line).…”
Section: Gastric Cancermentioning
confidence: 99%
“…34 Furthermore, it has been reported that fluoxetine possesses anticancer activity both in vitro and in vivo . 35 , 36 In addition, fluoxetine enhances the anticancer activity of certain chemotherapeutic anticancer drugs such as gemcitabine and paclitaxel. 37–39 …”
Section: Introductionmentioning
confidence: 99%